2019
DOI: 10.1128/mcb.00553-18
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Environment Promotes Barrier Formation in Human Intestinal Epithelial Cells through Regulation of MicroRNA 320a Expression

Abstract: Intestinal epithelial cells (IECs) are exposed to the low-oxygen environment present in the lumen of the gut. These hypoxic conditions on one hand are fundamental for the survival of the commensal microbiota and, on the other hand, favor the formation of a selective semipermeable barrier, allowing IECs to transport essential nutrients/water while keeping the sterile internal compartments separated from the lumen containing commensals. The hypoxia-inducible factor (HIF) complex, which allows cells to respond an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…Essential for the colonoid model, we found no differences in cell composition, morphology or cellular apoptosis suggesting that colonoids cultured under a physiological, low oxygen concentration were fully viable. Relevance to IBD is suggested by studies in experimental colitis models ( Sun et al, 2019 ; Colgan et al, 2020 ; Yin et al, 2020 ), and cell lines ( Muenchau et al, 2019 ; Vissenaekens et al, 2019 ), which indicate a protective stabilization of HIF1α, attenuating mucosal inflammation and promoting barrier formation. Moreover, reagents that activate HIF via inhibition of the prolyl hydroxylase enzymes, are suggested to induce hypoxia-mediated resolution in patients with intestinal mucosal inflammatory disease ( Glover and Colgan, 2011 ; Brown et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Essential for the colonoid model, we found no differences in cell composition, morphology or cellular apoptosis suggesting that colonoids cultured under a physiological, low oxygen concentration were fully viable. Relevance to IBD is suggested by studies in experimental colitis models ( Sun et al, 2019 ; Colgan et al, 2020 ; Yin et al, 2020 ), and cell lines ( Muenchau et al, 2019 ; Vissenaekens et al, 2019 ), which indicate a protective stabilization of HIF1α, attenuating mucosal inflammation and promoting barrier formation. Moreover, reagents that activate HIF via inhibition of the prolyl hydroxylase enzymes, are suggested to induce hypoxia-mediated resolution in patients with intestinal mucosal inflammatory disease ( Glover and Colgan, 2011 ; Brown et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is not only required for the microbiota but it also influences the epithelial cells themselves (118). It was shown that hypoxia favors barrier function in human intestinal epithelial cells (119). As it is well established that hypoxia in the tumor microenvironment affects the response of immune cells (118), it is critical to start investigating whether hypoxia could impact immune response of intestinal epithelial cells upon infection.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…miRNAs are singlestranded non-coding RNA molecules of approximately 22 nucleotides in length that play important roles in regulating gene expression and biological function (79). In recent years, studies have shown that EV-derived miRNA expression is related to gut microbiota and intestinal barrier function (80)(81)(82). Mice deficient in IECs miRNA showed intestinal dysbiosis and exacerbation of colitis, which ameliorated after transplantation with fecal EV-derived miRNA from wild-type mice (80).…”
Section: Extracellular Vesicle and Mirnamentioning
confidence: 99%